A Review of Recent HIV Prevention Interventions and Future Considerations for Nursing Science. (25th May 2021) - Threats, Megan; Brawner, Bridgette M.; Montgomery, Tiffany M.; Abrams, Jasmine; Jemmott, Loretta Sweet; Crouch, Pierre-Cedric; Freeborn, Kellie; Kamitani, Emiko; Enah, Comfort
Abstract: As our knowledge of HIV evolved over the decades, so have the approaches taken to prevent its transmission. Public health scholars and practitioners have engaged in four key strategies for HIV prevention: behavioral-, technological-, biomedical-, and structural/community-level interventions. We reviewed recent literature in these areas to provide an overview of current advances in HIV prevention science in the United States. Building on classical approaches, current HIV prevention models leverage intimate partners, families, social media, emerging technologies, medication therapy, and policy modifications to effect change. Although much progress has been made, additional work is needed to achieve the national goal of ending the HIV epidemic by 2030. Nurses are in a prime position to advance HIV prevention science in partnership with transdisciplinary experts from other fields (e.g., psychology, informatics, and social work). Future considerations for nursing science include leveraging transdisciplinary collaborations and consider social and structural challenges for individual-level interventions.